The Effect of Uncoated SPIONs on hiPSC-Differentiated Endothelial Cells - Salingova, Barbara; Simara, Pavel; Matula, Pavel; Zajickova, Lenka; Synek, Petr; Jasek, Ondrej; Veverkova, Lenka; Sedlackova, Miroslava; Nichtova, Zuzana; Koutna, Irena (International journal of molecular sciences, 2019)
BACKGROUND: Endothelial progenitor cells (EPCs) were indicated in vascular repair, angiogenesis of ischemic organs, and inhibition of formation of initial hyperplasia. Differentiation of endothelial cells (ECs) from human induced pluripotent stem cells (hiPSC)-derived endothelial cells (hiPSC-ECs) provides an unlimited supply for clinical application. Furthermore, magnetic cell labelling offers an effective way of targeting and visualization of hiPSC-ECs and is the next step towards in vivo studies. METHODS: ECs were differentiated from hiPSCs and labelled with uncoated superparamagnetic iron-oxide nanoparticles (uSPIONs). uSPION uptake was compared between hiPSC-ECs and mature ECs isolated from patients by software analysis of microscopy pictures after Prussian blue cell staining. The acute and long-term cytotoxic effects of uSPIONs were evaluated by MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay) and Annexin assay. RESULTS: We showed, for the first time, uptake of uncoated SPIONs (uSPIONs) by hiPSC-ECs. In comparison with mature ECs of identical genetic background hiPSC-ECs showed lower uSPION uptake. However, all the studied endothelial cells were effectively labelled and showed magnetic properties even with low labelling concentration of uSPIONs. uSPIONs prepared by microwave plasma synthesis did not show any cytotoxicity nor impair endothelial properties. CONCLUSION: We show that hiPSC-ECs labelling with low concentration of uSPIONs is feasible and does not show any toxic effects in vitro, which is an important step towards animal studies.
Keywords: železité sloučeniny; viabilita buněk; endoteliální buňky pupečníkové žíly (lidské); biologické markery; Endothelial Cells; reprogramming; endoteliální buňky; Ferric Compounds; Biomarkers; human induced pluripotent stem cell-derived endothelial cells; buněčná diferenciace; Cell Survival; imunohistochemie; Magnetite Nanoparticles; Human Umbilical Vein Endothelial Cells; Induced Pluripotent Stem Cells; mature endothelial cells; magnetické nanočástice; kultivované buňky; indukované pluripotentní kmenové buňky; lidé; superparamagnetic iron-oxide nanoparticles; Immunohistochemistry; Humans; differentiation; Cells, Cultured; Cell Differentiation